Praktik Transfer Pricing Perusahaan Sektor Manufaktur di Indonesia - Oktaviani, Rachmawati Meita; Wulandari, Sartika (Universitas Sains dan Teknologi Komputer, 2024)
Transfer pricing is a policy used when setting the transfer price of a transaction, whether it involves goods, services, intangible assets, or financial transactions, and is often practiced in the industrial world. The practice of transfer pricing can be reflected in aspects of tax planning, bonus mechanisms, the valuation of intangible assets, and tunneling incentives. This study aims to examine whether tax planning, bonus mechanisms, the determination of intangible asset values, and tunneling incentives are variables that influence transfer pricing practices. The population in this study consists of 136 industries, and 80 samples were obtained from manufacturing companies listed on the Indonesia Stock Exchange for the period of 2018-2021. The sample selection was conducted using purposive sampling with the following criteria: 1) manufacturing companies listed on the Indonesia Stock Exchange during the period of 2018-2021, 2) companies that did not incur losses during the observation years, 3) companies that have special relationships in the form of sales transactions with related parties, and 4) companies that record intangible assets. This research uses panel data analysis techniques with the assistance of EViews 9 tools. The research results indicate that tax planning, intangible assets, and tunneling incentives have a significant positive effect on transfer pricing. Meanwhile, the mechanism of bonuses has a negative but insignificant effect on transfer pricing